Gold silver alloy nanoparticles (GSAN): an imaging probe for breast cancer screening with dual-energy mammography or computed tomography. Issue 28 (5th July 2016) - Naha, Pratap C.; Lau, Kristen C.; Hsu, Jessica C.; Hajfathalian, Maryam; Mian, Shaameen; Chhour, Peter; Uppuluri, Lahari; McDonald, Elizabeth S.; Maidment, Andrew D. A.; Cormode, David P.
Abstract : GSAN have improved biocompatiblility and are effective DEM/CT contrast agents. Abstract : Earlier detection of breast cancer reduces mortality from this disease. As a result, the development of better screening techniques is a topic of intense interest. Contrast-enhanced dual-energy mammography (DEM) is a novel technique that has improved sensitivity for cancer detection. However, the development of contrast agents for this technique is in its infancy. We herein report gold–silver alloy nanoparticles (GSAN) that have potent DEM contrast properties and improved biocompatibility. GSAN formulations containing a range of gold : silver ratios and capped with m-PEG were synthesized and characterized using various analytical methods. DEM and computed tomography (CT) phantom imaging showed that GSAN produced robust contrast that was comparable to silver alone. Cell viability, reactive oxygen species generation and DNA damage results revealed that the formulations with 30% or higher gold content are cytocompatible to Hep G2 and J774A.1 cells. In vivo imaging was performed in mice with and without breast tumors. The results showed that GSAN produce strong DEM and CT contrast and accumulated in tumors. Furthermore, both in vivo imaging and ex vivo analysis indicated the excretion of GSAN via both urine and feces. In summary, GSAN produce strong DEM and CT contrast, and has potential for both blood pool imaging and for breast cancer screening.